Implementasi Peraturan BPJS Kesehatan Nomor 1 Tahun 2014 Tentang Penyelenggaraan Jaminan Kesehatan di kantor BPJS Kesehatan Cabang Gunungsitoli Kepulauan Nias Provinsi Sumatera Utara (Studi pada Pelayanan Kepesertaan - ELFIN OTOMOSI GULO (Universitas Negeri Surabaya, 2015)
THE IMPLEMENTATION OF BPJS 2014 NO. 1 REGULATION ON THE GUARANTEE OF HEALTH MANAGEMENT AT BPJS BRANCH OFFICE OF GUNUNGSITOLI NIAS ISLAND OF NORTH SUMATERA PROVICE (Study on Membership Services) Elfin Otomosi Gulo ABSTRACT To organize the health insurance, the health of BPJS issued the regulation of BPJS 2014 No. 1 on the management of health insurance. In the practice, there are many problems so that the management implementation of health insurance has not been completely worked as expected. This Thesis discusses on the implementation of health insurance in BPJS Branch Office of Gunungsitoli Nias Islands of North Sumatera Province. The goal of this discussion is to describe the implementation of BPJS regulation 2014 No. 1 on the implementation of health insurance in branch office of BPJS in Gunungsitoli Nias Island of North Sumatera province. The Description in this discussion using implementation theory of Donald Van Metter and Carl Van Horn, with six variables, which are the size and the purpose of policy, resources, the characteristics of implementing agent, attitude/tendency of implementing agent, inter-organizational communication and implementing activity and economy, social and politics environment. The type of this thesis is descriptive study. The technique of collecting data through observation, interviews and documentation. Subject of the research in this thesis are staff/employeesBPJS office, the doctors of health center and BPJS participants with the techniques of Miles and Hubberman interactive model analysis data. In the implementation of BPJS Regulation 2014 No. 1 on the Implementation of The Health Insurance Branch Office of BPJS Gunungsitoli Nias Islands North Sumatera that still not going well. This happens due to the lack of human resources at BPJS of Branch Gunungsitoli , the lack of medical personnel in hospitals and health centers of Nias Islands, unavailability of adequate facilities at the hospital or health center, the great coverage of the region, namely the four districts and one the city, the lack of communication and coordination between BPJS Branch Gunungsitoli with other enforcement agencies such as officers in public clinics and health centers still lack an explanation/dissemination to the public related to the implementation of health insurance. In conclusion, the implementation of BPJS Regulation 2014 No. 1 on the Implementation of the Health Insurance BPJS Branch Office of Gunungsitoli Nias Islands has been done, but there are many obstacles in its implementation. The advice given that BPJS Branch Office of Gunungsitoli shoud be added human resources, adding medical personnel, equip the lacking health facilities, increasing the number of BPJS office in each district city, improve communication and coordination to the other operators and the public in order to realize the better implementation of health guarantee for all people in Nias and facilitate the public in obtaining health care . Key Words: Implementation, Health Insurance